2019
DOI: 10.1111/sms.13465
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro investigation into the effects of 10 Hz cyclic loading on tenocyte metabolism

Abstract: Tendinopathy is a prevalent, highly debilitating condition, with poorly defined etiology. A wide range of clinical treatments has been proposed, with systematic reviews largely supporting shock wave therapy or eccentric exercise. Characterizing these treatments have demonstrated both generate perturbations within tendon at a frequency of approximately 8‐12 Hz. Consequently, it is hypothesized that loading in this frequency range initiates increased anabolic tenocyte behavior, promoting tendon repair. The prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Herein COL2A1 expression was the lowest of all genes evaluated by qPCR, indicating that even non-dynamic tensile forces (control group) inhibit COL2A1 transcription, consistent with previously reported absent expression of COL2A1 from tenocytes given 24 h of cyclic 1% strain at 10 Hz or in tendon fascicles. 35,36 For COL1 and COL3A1, a previous study in comparable fibrin hydrogels found that porcine MSCs subjected to 7 days of 10% cyclic tensile strain at 0.5 Hz increased COL1A1 but decreased COL3A1 expression. 12 In other scaffolds alterations in COL1 and COL3A1 gene expression have been reported.…”
Section: Discussionmentioning
confidence: 96%
“…Herein COL2A1 expression was the lowest of all genes evaluated by qPCR, indicating that even non-dynamic tensile forces (control group) inhibit COL2A1 transcription, consistent with previously reported absent expression of COL2A1 from tenocytes given 24 h of cyclic 1% strain at 10 Hz or in tendon fascicles. 35,36 For COL1 and COL3A1, a previous study in comparable fibrin hydrogels found that porcine MSCs subjected to 7 days of 10% cyclic tensile strain at 0.5 Hz increased COL1A1 but decreased COL3A1 expression. 12 In other scaffolds alterations in COL1 and COL3A1 gene expression have been reported.…”
Section: Discussionmentioning
confidence: 96%
“…To this end, various biophysical (e.g. surface topography [ 22 , 23 ], mechanical stimulation [24] ), biochemical (e.g. physiological low oxygen tension [25] , media supplements [26] ), biological (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[34] Under physiological conditions, the strain rate of the tendon is around 0.1-0.5 Hz; however, during intense activity, the frequency can be as high as 10 Hz. [35,36] Recently, it has been demonstrated that tendon cells modulate their gene expression, protein synthesis and mitogenesis in vitro through activation of mechanotransductive signaling pathways under physiological mechanical stimulation. [37] Therefore, we compared the effect of mechanical and electromechanical stimulation on human hTDCs gene and protein expression (Table 3, 4 and 5) (Figure 5).…”
Section: The Effect Of Electromechanical Stimulation On Tendon-specif...mentioning
confidence: 99%